Density Functional Theory Study of Intermolecular Interactions between Amylum and Cellulose - Raynardthan Pontoh; Vania Edita Rarisavitri; Christine Charen Yang; Maximilliam Febriand Putra; Daru Seto Bagus Anugrah (Universitas Gadjah Mada, 2022)
Amylum is one of the polysaccharides developed into biodegradable plastic bags. However, amylum-based plastics are easily damaged due to their low mechanical strength and hydrophilic properties. Cellulose is used as a support material in amylum-based plastics to increase strength and reduce water damage. This study investigated the molecular interactions between amylum and cellulose computationally. The minimum interaction energy of amylum and cellulose was calculated using in silico modeling using the Density Functional Theory (DFT) method. The B3LYP function and the basis set 6-31++g** were used in the calculations. Simultaneously, D3 Grimme dispersion correction was used as the effect of water solvent in the measures. The results obtained from this study were the interaction energy of amylum and cellulose of –29.8 kcal/mol. The HOMO-LUMO energy gap of the cellulose-amylum complex was lower than cellulose, indicating that the cellulose-amylum complex was more reactive and bonded to each other. Analysis of Natural Bond Orbital (NBO), Quantum Theory Atom in Molecule (QTAIM), Reduced Density Gradient (RDG), Non-covalent Interaction Index (NCI), and Intrinsic Bond Strength Index (IBSI) showed that the cellulose-amylum complex had weak to medium intermolecular bonds. The hydrogen bond at O61···H48 was the strongest in the complex. All data show that cellulose and amylum could interact through non-covalent bonds.